Rola układu endokannabinoidowego w fizjologicznych i patologicznych procesach w gałce ocznej - Nadolska, Krystyna; Goś, Roman (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Plant of Cannabis sativa/ marihuana except for its psychotropic effects possesses a range of pharmacological properties, that has been utilized for medical purposes over a period of millenia. Investigations concerning biochemical mechanism of action of the main and most active pharmacological compound of Cannabis sativa, cannabinoid Δ9-THC, contributed to the discovery of cannabinoid receptors both in the central nervous system (CNS) and peripheral tissues, that mediated actions of this substance. The discovery made possible identification of a new, endogenous signaling system reffered to as the endocannabinoid system. Besides cannabinoid receptors CB1 and CB2, the system includes it’s endogenic ligands (endocannabinoids) and compounds that participate in their biosynthesis and inactivation. Structure and functioning of the endocannabinoid system is conservative in all vertebrates. It’s activation with plant, synthetic and endogenous cannabinoids has an influence on multiple physiological and pathological processes within the eye.